Patterns-of-Care Analysis for Radiotherapy of Elderly Head-and-Neck Cancer Patients: A Trinational Survey in Germany, Austria and Switzerland - Haehl, Erik; Rühle, Alexander; Spohn, Simon; Sprave, Tanja; Gkika, Eleni; Zamboglou, Constantinos; Grosu, Anca-Ligia; Nicolay, Nils H. (Frontiers in Oncology, 2022)
Objectives The number of elderly head-and-neck squamous cell carcinoma (HNSCC) patients is increasing, and clinical trials defining the standard of care either excluded or underrepresented elderly patients. This leaves physicians with a challenging and highly individual treatment decision largely lacking clinical evidence. Methods A tri-national patterns-of-care survey was sent to all members of the German (DEGRO), Austrian (ÖGRO), and Swiss (SRO/SSRO) national societies of radiation oncology. The online questionnaire consisted of 27 questions on the treatment of elderly HNSCC patients, including 6 case-based questions. Frequency distributions and subgroup comparisons were calculated using SPSS statistics software. Results A total of 132 answers were collected, including 46(35%) form universities, 52(39%) from non-university-hospitals and 34(26%) from private practices. 83(63%) treat 1-5 and 42(32%) >5 elderly HNSCC patients per month. Target volumes are defined analog current guidelines by 65(50%) of responders and altered based on age/comorbidities or tumor stage by 36(28%) and 28(22%), respectively. Chemotherapy is routinely administered by 108(84%) if indicated, with weekly 40mg/m2 of cisplatin being the favored regimen by 68(53%) in the definitive situation and 60(47%) in the adjuvant setting. Hypofractionation and hyperfractionation/acceleration are used by 26(20%) and 11(9%), respectively. Only 7(5%) clinicians routinely recommend inpatient treatment for elderly HNSCC patients. In a typical definitive patient case, 73(63%) responders recommended chemoradiation with bilateral elective node irradiation analog current guidelines. In an adjuvant example case recommendations regarding elective volume and chemotherapy were heterogeneous. Differences between responders’ institutions concern the frequency of PET-CT in staging, preventive port-catheter and PEG implantation, the choice of chemotherapy regimens and the use of alternative fractionations. Conclusion Treatment of elderly HNSCC-patients in the German-speaking countries mainly follows guidelines established for younger patients. Algorithms for patient stratification and treatment de-escalation for “unfit” elderly patients are needed.